Multi-criteria decision analysis for optimal sugarcane land allocation in Merauke, South Papua, Indonesia - OMO RUSDIANA; SELAMET KUSDARYANTO; WIDHYANTO MUTTAQIEN; MACHFUD MACHFUD; IRBA DJAJA (Asian Journal of Agriculture, 2025)
Abstract. Rusdiana O, Kusdaryanto S, Muttaqien W, Machfud, Djaja I. 2025. Multi-criteria decision analysis for optimal sugarcane land allocation in Merauke, South Papua, Indonesia. Asian J Agric 9: 689-701. Achieving sustainable sugarcane expansion requires integrating biophysical suitability with social and environmental considerations. This study applied a Multi-Criteria Decision Analysis (MCDA) using the Simple Additive Weighting (SAW) method to identify optimal areas for sugarcane cultivation in Merauke, South Papua, Indonesia. The analysis incorporates multiple criteria, including biophysical factors (climate, soil type, topography), land use policies (zoning, conservation areas), and social factors (land rights, indigenous communities' territories). Data were collected through field surveys, stakeholder interviews, and spatial analysis using Geographic Information Systems (GIS). The results indicate that approximately 80% of the study area is biophysically suitable for sugarcane cultivation. However, when considering land use policies, the available area reduces to 43.77% due to the presence of protected areas, forests, and risk-prone zones. After factoring in the rights of indigenous communities and areas of cultural significance, the land available for sugarcane cultivation shrinks further, leaving only 38.16% of the land as suitable for development. This highlights the trade-off between agricultural expansion and environmental conservation, as well as the importance of respecting indigenous land rights in land use planning. The study highlights the importance of combining geospatial analysis and stakeholder input for policymakers, land planners, and agricultural and forest developers to guide evidence-based, sustainable agricultural expansion in emerging regions.